Characterization of the human granulocyte-macrophage colony-stimulating factor promoter region by genetic analysis: correlation with DNase I footprinting. - Nimer, S D (1988)
T-cell activation induces expression of the hematopoietic growth factor granulocyte-macrophage colony-stimulating factor (GM-CSF). To define the molecular events involved in the induction of GM-CSF gene expression more clearly, we prepared and analyzed deletion mutants of GM-CSF promoter recombinant constructs. The results localized inducible expression to a 90-base-pair region (-53 to +37) which is active in uninfected and human T-cell leukemia virus-infected T-cell lines but not in resting or mitogen-stimulated B cells. DNase I footprinting experiments revealed protection of sequences contained within this region, including a repeated nucleotide sequence, CATT(A/T), which could serve as a core recognition sequence for a cellular transcription factor. Upstream of these GM-CSF promoter sequences is a 15-base-pair region (-193 to -179) which has negative regulatory activity in human T-cell leukemia virus-infected T cells. These studies revealed a complex pattern of regulation of GM-CSF expression in T cells; positive and negative regulatory sequences may play critical roles in controlling the expression of this potent granulopoietin in the bone marrow microenvironment and in localized inflammatory responses.